Unveiling students’ learning strategies and barriers to extensive reading: a case study in an Indonesian university - Luthfaturrohmah (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2024)
The present study aims to investigate students’ learning strategies and barriers encountered in extensive reading activities. This research was designed with a qualitative case study method. The study recruited six Indonesian university EFL students majoring in English language education to participate and a lecturer in the study program. Data were garnered through semi-structured interviews as a data collection method. The data were analyzed thematically to find emerging themes. The research findings demonstrate that the EFL students employed three extensive reading comprehension strategies. The three strategies included predicting by inferring the meaning of unfamiliar words by making guesses based on the context, guessing from context by utilizing previous knowledge about the topics in the text, and paraphrasing by creating sentences from the obtained information. Another finding also uncovers the university students’ barriers in extensive reading, including the students’ language background and lack of interest in reading. This study concludes with practical implications for how EFL students engage in extensive reading with various learning strategies and how university teachers boost their students’ interests in more diverse extensive reading activities.